Pengaruh Kepercayaan Kepada Atasan, Job Embeddedness, dan Kepuasan Kerja Terhadap Kepercayaan Karyawan Kepada Organisasi: The Influence of Trust In Leader, Job Embeddedness, and Job Satisfaction on Organizational Trust - Mauli Melda Manihuruk; Tjiptogoro Dinarjo Soehari (School of Business, Bogor Agricultural University (SB-IPB), 2020)
This study analyzes the effect of trust in superiors, work attachment and job satisfaction on employee confidence in the organization. This type of research is quantitative. The population is all employees. The sampling technique using non probability sampling method with the type used is purposive sampling (using the Slovin formula with an error of 5% obtained a sample of sixty seven employees). The method used in this study is multiple linear regression using data processing software tools SPSS version 24.0. The results showed that trust in superiors, work attachment and job satisfaction together (simultaneously) significantly influence employee confidence in the organization. Partially job attachment and job satisfaction have a significant positive effect on employee trust in the organization while trust in superiors has a significant negative effect on employee trust in the organization. Job satisfaction is the most influential variable on employee trust in the organization after the variable work attachment and trust in superiors. The suggestion for the company is that the company should further increase work attachment and employee job satisfaction to obtain high employee trust. Keywords: job embeddedness, trust in leader, job satisfaction, organizational trust